Предмет: Алгебра,
автор: Кристина211298
Помогите еще раз упростить, пожалуйста
Приложения:
![](https://files.topotvet.com/i/210/2100232674db33527fd638254998e458.jpg)
Ответы
Автор ответа:
0
3х^2-5х-25
сподіваюсь, що так
сподіваюсь, що так
Автор ответа:
0
і ще врахувати ОДЗ
Автор ответа:
0
= ( 3х(х-4) - 3х) (х-4) : ( х (х-4) - 6х+25) (х-4)=
(3х²-12х-3х) (х-4) * (х-4) (х²-4х-6х+25) =
(3х²-15х) ( х²-10х+25) =
3х ( х-5) (х-5)² = 3х (х-5)
(3х²-12х-3х) (х-4) * (х-4) (х²-4х-6х+25) =
(3х²-15х) ( х²-10х+25) =
3х ( х-5) (х-5)² = 3х (х-5)
Похожие вопросы
Предмет: Химия,
автор: Аноним
Предмет: Литература,
автор: ruzannaatanesan547
Предмет: Литература,
автор: Аноним
Предмет: Биология,
автор: ollk